2021
DOI: 10.1038/s41598-021-87168-0
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omic analyses in Abyssinian cats with primary renal amyloid deposits

Abstract: The amyloidoses constitute a group of diseases occurring in humans and animals that are characterized by abnormal deposits of aggregated proteins in organs, affecting their structure and function. In the Abyssinian cat breed, a familial form of renal amyloidosis has been described. In this study, multi-omics analyses were applied and integrated to explore some aspects of the unknown pathogenetic processes in cats. Whole-genome sequences of two affected Abyssinians and 195 controls of other breeds (part of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 82 publications
2
13
0
Order By: Relevance
“…Due to the conserved amyloidogenic nature of A-SAA, domestic animals develop systemic amyloidosis similarly to humans 2,33,34 . Among cats, Siamese and Abyssinian breeds were reported as particularly prone to amyloidosis due to a familial predisposition [35][36][37][38][39][40] . Strikingly, the close-to-extinct captive cheetah, from whose lineage DSH cat ancestors split about six million years ago, suffers from an extreme disease prevalence of 70%, likely facilitated by prion-like disease transmission [41][42][43][44] .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the conserved amyloidogenic nature of A-SAA, domestic animals develop systemic amyloidosis similarly to humans 2,33,34 . Among cats, Siamese and Abyssinian breeds were reported as particularly prone to amyloidosis due to a familial predisposition [35][36][37][38][39][40] . Strikingly, the close-to-extinct captive cheetah, from whose lineage DSH cat ancestors split about six million years ago, suffers from an extreme disease prevalence of 70%, likely facilitated by prion-like disease transmission [41][42][43][44] .…”
Section: Introductionmentioning
confidence: 99%
“…44 The bond between SAA and apolipoproteins occurs through the SAA N-terminal fragment and prevents SAA misfolding because the unbound SAA is labile and prone to conformational change. [45][46][47] Of note, apolipoproteins have been observed in kidneys from humans, cats, and island foxes with renal AA amyloidosis, including apolipoproteins A-I, A-IV, and E. 26,27,48 Thus, they also might play an important role in shelter cats with the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, proteomics‐based technologies have played a pivotal role in the characterization of amyloid structure and related proteins in humans and animals 23‐25 . In 2 recent studies, apolipoprotein (Apo) E, Apo A‐I, and Apo I‐V were identified in renal samples from Abyssinian, Siamese and DSH cats with AA amyloidosis 26,27 . To the best of our knowledge, proteomics analysis of urine samples in cats with AA amyloidosis has not been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…However, several hypotheses have been proposed, such as increased circulating concentrations of SAA along with defects in the degrading properties of monocytes or genetic structural abnormalities of proteins [3]. Many conditions, including neoplastic, inflammatory, and metabolic diseases are associated with high production of SAA in cats [9] but amyloidosis has been only sporadically reported in not predisposed breeds [10][11][12][13]; recently, the differences in SAA genetic sequences proved to not contribute to the pathogenesis of feline AA-amyloidosis both in Japanese domestic cats [14] and in Abyssinian breed [15]. Other factors, such as amyloidenhancing factors and glycosaminoglycans, may possibly take part in amyloidogenesis by accelerating amyloid-fibril deposition [16].…”
Section: Introductionmentioning
confidence: 99%